2021
DOI: 10.1155/2021/9987844
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Mechanisms of the Oligopeptides (FWKVV and FMPLH) from Muscle Hydrolysate of Miiuy Croaker against Oxidative Damage of HUVECs

Abstract: In this work, the antioxidant mechanisms of bioactive oligopeptides (FWKVV and FMPLH) from protein hydrolysate of miiuy croaker muscle against H2O2-damaged human umbilical vein endothelial cells (HUVECs) were researched systemically. The finding demonstrated that the HUVEC viability treated with ten antioxidant peptides (M1 to M10) at 100.0 μM for 24 h was not significantly affected compared with that of the normal group ( P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…To evaluate the antioxidative abilities of 12 isolated APs (TRP1 to TRP12), radical scavenging assay, Ferricreducing power, lipid peroxidation inhibition assay, and cytoprotection on H 2 O 2 -damaged Chang live cells were conducted. (18,19), loach (PSYV: 17.0 mg/ml) (52), skipjack tuna head (ERGPLGPH: 0.93 mg/ml; DAGPYGPI: 1.33 mg/ml; VEE: 3.76 mg/ml) (6), and Salmo salar pectoral fin (TTANIEDRR: 2.503 mg/ml) (53). Therefore, TRP3, TRP4, TRP7, TRPH8, TRPH9, and TRP12 could strongly hold back the DPPH• reaction by donating hydrogens or directly clearing away free radicals.…”
Section: Antioxidant Activity Of 12 Isolated Aps (Trp1 To Trp12)mentioning
confidence: 99%
See 4 more Smart Citations
“…To evaluate the antioxidative abilities of 12 isolated APs (TRP1 to TRP12), radical scavenging assay, Ferricreducing power, lipid peroxidation inhibition assay, and cytoprotection on H 2 O 2 -damaged Chang live cells were conducted. (18,19), loach (PSYV: 17.0 mg/ml) (52), skipjack tuna head (ERGPLGPH: 0.93 mg/ml; DAGPYGPI: 1.33 mg/ml; VEE: 3.76 mg/ml) (6), and Salmo salar pectoral fin (TTANIEDRR: 2.503 mg/ml) (53). Therefore, TRP3, TRP4, TRP7, TRPH8, TRPH9, and TRP12 could strongly hold back the DPPH• reaction by donating hydrogens or directly clearing away free radicals.…”
Section: Antioxidant Activity Of 12 Isolated Aps (Trp1 To Trp12)mentioning
confidence: 99%
“…The EC 50 values of TRP3, TRP4, TRPH7, TRPH9, and TRP12 on HO• were 0.456 ± 0.015, 0.536 ± 0.021, 0.476 ± 0.051, 0.369 ± 0.052, and 0.413 ± 0.019 mg/ml, respectively, which were notably less than those of other seven isolated APs (p < 0.05) (Table 3). In addition, the EC 50 values of TRP6, TRP7, TRPH8, TRPH9, and TRP17 were less than those of APs from miiuy croaker swim bladders (0.68, 2.31, 2.35, 2.45, and 2.85 mg/ml for FPYLRH, FTGMD, GFYAA, FSGLR, and VPDD, respectively) (50), Antarctic krill (VEKGK: 1.63 mg/ml; SGPA: 2.36 mg/ml; NWDDMRIVAV: 2.61 mg/ml; NGPDPRPSQQ: 2.74 mg/ml) (18,19), Misgurnus anguillicaudatus (PSYV: 2.64 mg/ml) (52), and Raja porosa cartilages (IVAGPQ: 5.03 mg/ml) (13). The present finding indicated that the APs from TRPH, especially TRP3, TRP4, TRPH7, TRPH9, and TRP12, could effectively clear HO• to protect biological macromolecules in cells from the oxidative damage induced by HO•.…”
Section: Antioxidant Activity Of 12 Isolated Aps (Trp1 To Trp12)mentioning
confidence: 99%
See 3 more Smart Citations